GmPGL2, Encoding a Pentatricopeptide Repeat Protein, Is Essential for Chloroplast RNA Editing and Biogenesis in Soybean - Feng, Xingxing; Yang, Suxin; Zhang, Yaohua; Zhiyuan, Cheng; Tang, Kuanqiang; Li, Guang; Yu, Hui; Leng, Jiantian; Wang, Qingyu (Frontiers in Plant Science, 2021)
Chloroplast biogenesis and development are highly complex processes requiring interactions between plastids and nuclear genomic products. PPR (pentatricopeptide repeat) proteins play an essential role in the development of chloroplasts, it is not clear how RNA editing factors influence soybean development. In this study, a Glycine max pale green leaf 2 mutant (Gmpgl2) was identified with decreased chlorophyll contents. Genetic mapping revealed that a single nucleotide deletion at 1949 bp of the Glyma.05g132700 gene in the Gmpgl2 mutant resulted in a truncated GmPGL2 protein. The nuclear-encoded GmPGL2 is a PLS-type PPR protein that localizes to the chloroplasts. The C-to-U editing efficiencies of rps16, rps18, ndhB, ndhD, ndhE, and ndhF were reduced in Gmpgl2 mutant. REMSA experiment showed that GmPGL2 bound to the immediate upstream sequences at RNA editing sites of rps16 and ndhB in vitro respectively. In addition, GmPGL2 was found to interact with GmMORF8, GmMORF9, and GmORRM6. These results suggest that GmPGL2 participates in C-to-U RNA editing via the formation of a complex RNA editosome in soybean chloroplasts.